Efficacy and tolerability of infliximab retreatment in patients with inflammatory bowel disease: a systematic review and meta-analysis - Seungwon Yang; Siyoung Yang; Young Kwon Jo; Seungyeon Kim; Min Jung Chang; Junjeong Choi; Jae Hee Cheon; Yun Mi Yu (SAGE Publishing, 2021)
Background: A large proportion of patients with inflammatory bowel disease (IBD) relapse after drug discontinuation despite achieving a stable state of infliximab-induced clinical remission. Resuming the use of the same tumor necrosis factor-alpha (TNF-α) inhibitors in patients who relapse following TNF-α inhibitor discontinuation was suggested as a treatment strategy. We conducted a systematic review and meta-analysis to evaluate the efficacy and safety of infliximab retreatment in patients with IBD. Methods: A systematic literature search to shortlist relevant studies was conducted using the MEDLINE, Embase, CINAHL, and SCOPUS databases for studies published from inception to August 2020. Results: Nine studies were included in the meta-analysis. The pooled clinical remission rate of infliximab retreatment in patients with IBD was 85% (95% confidence interval (CI), 81-89%) for induction treatment and 73% (95% CI, 66-80%) for maintenance treatment. A clinical remission rate following infliximab reintroduction was achieved in a greater proportion of patients with Crohn's disease (87%; 95% CI, 83-91%) than in those with ulcerative colitis (78%; 95% CI, 61-91%) for induction treatment, but the difference was not statistically significant. Infusion-related reactions after infliximab retreatment occurred in 9% of patients with IBD (95% CI, 3-16%). Conclusion: Infliximab retreatment showed high clinical remission rates with tolerable infusion-related reactions in patients with IBD who achieved remission with initial infliximab treatment but relapsed after its discontinuation. We suggest infliximab as a viable alternative in patients with IBD who previously responded well to infliximab treatment.